Structural characterization and protective effect against renal fibrosis of polysaccharide from Ligustrum lucidum Ait. (10th February 2023) - Zhang, Jia-Li; Du, Chen; Poon, Christina Chui-Wa; He, Ming-Chao; Wong, Man-Sau; Wang, Na-Ni; Zhang, Yan
Abstract: Ethnopharmacological relevance: Fructus Ligustri Lucidi (FLL), the fruit of Ligustrum lucidum Ait., is a traditional Chinese medicine that has been used for tonifying the kidney and liver for decades. Aim of the study: This study aimed to explore and identify polysaccharides from FLL and elucidate its protective effect against renal fibrosis. Materials and methods: Polysaccharides were extracted and isolated from FLL. The purified fraction was identified by serial phytochemical work, such as gel-permeation chromatography, ion chromatography, gas chromatography-mass spectrometry, and nuclear magnetic resonance. Mice with unilateral ureteral obstruction (UUO) were applied as a renal fibrosis model. The male UUO mice were pretreated with heteropolysaccharide (Poly) 1 week prior to surgery and continuously treated for 7 days after the operation. Renal fibrosis was assessed by Periodic Acid-Schiff (PAS) staining and Masson's trichrome staining in paraffin-embedded slides. The murine mesangial cells SV40-MES13 upon angiotensin II (Ang II) treatment were developed as an in vitro fibrotic model. The cells were treated by Poly in the presence of Ang II. Molecular expression was detected by RT-PCR, immunoblotting, and immunofluorescence staining. Results: We identified a heteropolysaccharide composed of arabinose and galactose (molar ratio, 0.73:0.27) with a predicted chemical structure characterized by a backbone composed of 1, 5-α-Ara f, 1, 3, 5-α-Ara f, 1, 6-α-Gal p, and 1, 3, 6-β-Gal p and side chains comprised of T-α-Ara f, T-α-Ara p, and 1, 3-α-Ara f . Pretreatment of UUO mice with Poly effectively alleviated glomerulosclerosis and tubulointerstitial fibrosis. Moreover, Poly pretreatment down-regulated the expression of extracellular matrix (ECM) protein fibronectin (FN), profibrotic factor VEGF, proinflammatory cytokines MCP-1 and Rantes in the obstructed kidney. Similarly, the incubation of SV40-MES13 cells with Poly significantly inhibited Ang II-induced elevation in accumulation and expression level of FN and attenuated Ang II-evoked up-regulation in protein expression of MCP-1 and Rantes. Conclusions: Our study isolated and identified a naturally occurring heteropolysaccharide in FLL and revealed its potential in protecting the kidneys from fibrosis. Graphical abstract: Image 1 Highlights: A heteropolysaccharide (Poly) was isolated and purified from Fructus Ligustri Lucidi. The heteropolysaccharide consists of arabinose and galactose (0.73:0.27). Poly repressed glomerulosclerosis and tubulointerstitial fibrosis of UUO mice. Poly inhibited Ang II-evoked induction of profibrotic cytokines.